Journal Implications for the Decision of Sharia Economic Case Number 5K/Ag/2023 - Dhea Andini Nathania; Syifa Rahmalia Ridwani; Nurhasanah Nurhasanah; Udin Saripudin (Al-Iqtishadiyah: Ekonomi Syariah dan Hukum Ekonomi Syariah, 2024)
Islamic economics is experiencing a rapid expansion, which may lead to inevitable conflicts.  In Indonesia, the religious court is the authorized legal institution designated to resolve financial disputes related to Sharia law. Religious courts are authorized to settle financial disputes related to sharia in accordance with Law No. 7 of 1989 regarding Religious Courts and Law No. 3 as of 2006. The aim of this study is to gain a deeper understanding of the resolution of default disputes through the Supreme Court's decision titled "Implications for Arguments and Considerations in the Decision on Sharia Economic Disputes Number 5K/Ag/2023". A descriptive qualitative method was employed to conduct this research. This methodology focuses on collecting data and conducting in-depth analyses to comprehend the studied phenomenon. The findings of this study indicate that the decision of the judex facti/mahkamah sha'riyah Aceh is in accordance with the law, and therefore the cassation petition filed by the appellant must be denied. Objective analysis shows that the case was handled lawfully, without any violation of legal regulations or principles.Keywords: Sharia Economic Law, Religious Courts, Case Law